2000
DOI: 10.1007/s002130050045
|View full text |Cite
|
Sign up to set email alerts
|

Repeated ECS and fluoxetine administration have equivalent effects on hippocampal synaptic plasticity

Abstract: Given that fluoxetine and rECS share antidepressant properties, but differ in their effects on learning and memory, we propose that the common effects on dentate connectivity and synaptic plasticity described here are more likely to relate to affective rather than cognitive function. This result is consistent with other experiments showing that a reduction in dentate connectivity correlates with stress susceptibility in animals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
70
3
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(81 citation statements)
references
References 34 publications
6
70
3
2
Order By: Relevance
“…Different antidepressants and electroconvulsive therapy have been shown to effectively modulate synaptic plasticity in the dentate gyrus and the CA1 and in the neostriatum (De Murtas et al, 2004;Stewart and Reid, 2000). Here we found an impaired ability to induce LTP in a brain circuit that may be crucially involved in the pathophysiology of major depression (Nestler and Carlezon, 2006).…”
Section: Cms and Win55212-2 Effects On Plasticitymentioning
confidence: 55%
“…Different antidepressants and electroconvulsive therapy have been shown to effectively modulate synaptic plasticity in the dentate gyrus and the CA1 and in the neostriatum (De Murtas et al, 2004;Stewart and Reid, 2000). Here we found an impaired ability to induce LTP in a brain circuit that may be crucially involved in the pathophysiology of major depression (Nestler and Carlezon, 2006).…”
Section: Cms and Win55212-2 Effects On Plasticitymentioning
confidence: 55%
“…A recent electrophysiological study has also demonstrated that chronic ADs increase the field excitatory postsynaptics potentials connectivity in the dentate gyrus, effects which could represent an increase in synaptic connections and number of new neurons in the dentate gyrus granule cell layer. 112 …”
Section: Influence Of Antidepressant Treatment On Cell Survival Pathwaysmentioning
confidence: 99%
“…43 To circumvent the potential problem of cognitive deficits with tricyclic antidepressant drugs, 44 we examined the effects of chronic fluoxetine, a selective serotonin reuptake inhibitor that does not impair cognitive function, on both hippocampal synaptic plasticity and spatial learning. 45 Rats were given a course of eight ECS treatments spaced at 48-h intervals or 15 days of daily injections with fluoxetine (1 mg kg −1 , IP). Control groups were given anaesthesia alone or vehicle injections.…”
Section: Molecular Mechanisms Underlying the Ecs Effectmentioning
confidence: 99%